2011
DOI: 10.1055/s-0031-1300156
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Effects of Fluoxetine and Tianeptine, Two Antidepressants with Opposite Action Mechanisms, in Rats

Abstract: The behavioural effects of two antidepressants with opposite molecular mechanisms, tianeptine 7-[(3-chloro-6,11-dihydro-6-methyldibenzo[c,f][1,2]thiazepin - 11-yl)amino]heptanoic acid S,S-dioxide, CAS 66981-73-5) 5 mg/kg p.o., a serotonin reuptake enhancer, and fluoxetine (+/-)-N-methyl-3-phenyl-3-[(alpha, alpha, alpha-trifluoro-p- tolyl)oxy]propylamine, CAS 54910-89-3) 5 mg/kg p.o., a serotonin reuptake inhibitor, were compared after single and prolonged administration (7 and 14 days) once daily). In all expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…It was expected that the rats treated with SERT would improve their shocks avoidance. In a stressful situation, 5-HT should help to establish behavioural alterations in the most appropriate direction [51] [52]. Nevertheless, the present results strengthen past reports in the sense that learning is affected by drug treatment with serotonin precursors (e.g.…”
Section: The Effects Of Sertralinesupporting
confidence: 81%
“…It was expected that the rats treated with SERT would improve their shocks avoidance. In a stressful situation, 5-HT should help to establish behavioural alterations in the most appropriate direction [51] [52]. Nevertheless, the present results strengthen past reports in the sense that learning is affected by drug treatment with serotonin precursors (e.g.…”
Section: The Effects Of Sertralinesupporting
confidence: 81%
“…We found that the administration of clomipramine, fluoxetine, or sertraline resulted in decreased latency time of MWM test, thereby suggesting that these drugs result in improved memory performance in this model of AD. Other researchers have reported improved reference memory (food finding time in the maze) after chronic treatment with 5 mg/kg fluoxetine (Nowakowska et al 2000). In a status epilepticus model of mesial temporal lobe epilepsy in rats, fluoxetine treatment resulted in reversal of the learning deficit (though not the accelerated forgetting) (Barkas et al 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Anxiolytic effect is usually observed after combined administration of MAO A and MAO B inhibitors [6] or after chronic administration of MAO A inhibitor (moclobemide) [5,8], when the effects not directly related to MAO A inhibition appear [9]. The interaction of afobazole with MAO A along with the data on the binding of this agent with σ 1 and MT 1 receptors prompt further investigation of its antidepressant effects.…”
Section: Resultsmentioning
confidence: 99%